EL SUBSISTEMA REDUCCIONAL JESUÍTICO DEL BORDE ORIENTAL DE LAS PAMPAS Y SU VÍNCULO REGIONAL CON LOS ESTABLECIMIENTOS PRODUCTIVOS DE BUENOS AIRES, 1740-1753 - Fabian Arias (Boletín Geográfico)
The regional level that are interested in analyzing in this work is the space reduccional that organized the Society of Jesus in the south of the colonial jurisdiction of Buenos Aires, in the Salado river, between 1740-1753; in the same was founded three reductions: Nuestra Señora de la Concepción de los Pampas, Nuestra Señora del Pilar de Los Serranos and Nuestra Señora de los Desamparados Tuelchus. The hypothesis that suggests how shaft, proposes that the College of Buenos Aires, the productive units that existed in the Buenos Aires campaña (chacras and estancias) and missions located in the frontier border conformed an fate of sub-unit, which in the analytical purposes is called ‘cell jesuit of Buenos Aires’, which was connected with other subunits of similar characteristics throughout the Jesuit Province of Paraguay in the mid-eighteenth century. From this perspective it is further proposed that the missions of Pampas would be inserted in a network of reductions the Company of Jesus maintained colonial space Río de la Plata, which as a whole are sustained from the existence of the regional economic activities. The shaft suggested from what has been called the ‘cell jesuit of Buenos Aires’ can be understood, and at the same time analyze, considering that each establishment of the company forms part of “a group of units of production, distribution and consumption that operate from a common activity to all of them” (Rofman , 1984: 43). That situation is transformed to the cell in a subsystem, interconnected with other subsystems-cells along the Jesuit province of Paraguay.